Discussing Sharing Investment in Vietnam - Duc, Luu Huu (Business and Economic Research, 2024)
<p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The emergence of sharing investment within the landscape of the sharing economy presents a transformative market model blending ownership and resource utilization. This research delves into the tech-driven and collaborative nature of sharing investment, drawing upon seminal works and the evolving economic terrain of Vietnam. It offers nuanced insights into the multifaceted dimensions, implications, and challenges stemming from regulatory gaps and complex responsibilities. Highlighting the necessity for an inclusive and transparent framework, the research advocates for flexible policies to harness the potential benefits of sharing investments while navigating inherent challenges. Through a thorough analysis, this study lays a foundation for future research and policy development in the dynamic realm of investment sharing in Vietnam. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">In addition to the foundational aspects, recent empirical findings underscore the revolutionary potential of sharing investment in Vietnam’s by embracing cooperative ownership structures, technological integration, and community-centric approaches, sharing investment promises to foster financial inclusion, catalyze economic growth, and bolster societal welfare. However, realizing this potential necessitates overcoming several obstacles and establishing robust legislative frameworks. Regulatory adaptations must account for the innovative nature of sharing investments, safeguarding investors and ensuring market stability. In leveraging these strategies and capitalizing on the educated and technologically literate populace, Vietnam can harness the benefits of cooperative financial strategies, fostering equitable economic growth and societal advancement.